Silica and Biochar Amendments Improve Cucumber Growth under Saline Conditions - Manar Al-Toobi; Rhonda R. Janke; Muhammad Mumtaz Khan; Mushtaque Ahmed; Waleed M. Al-Busaidi; Abdul Rehman (Soil Systems, 2023)
Rapidly increasing salinization of arable land is a major threat to crop production globally, and the soil of regions with arid environments, such as Oman, are more prone to this menace. In this work, two complementary studies were carried out to evaluate the effect of soil amendments on soil physicochemical properties and growth of cucumber seedlings. In the first study, high- and low-saline soils were used with or without perlite. The amendments tested included mango wood biochar, silica, and biochar + silica, while no amendment was taken as the control. The second study included two cucumber cultivars and irrigation water with two salinity treatments, along with the same four soil amendments. The results showed that soil amendment with biochar alone or with silica enhanced the soil organic matter and NO3, P, and K concentration, while silica amendment substantially enhanced the soil Si level in both studies. Saline soil and irrigation water inhibited seedling emergence and plant growth in both experiments. However, the addition of biochar and silica alone or in combination increased the cucumber seedling dry weight from 39.5 to 77.3% under salt stress compared to the control. Likewise, silica and biochar + silica reduced the sap Na accumulation by 29–31.1% under high salinity. Application of biochar under high salinity resulted in 87.2% increase in sap K. Soil amendments with biochar and silica or their combination have the potential to reduce the adverse effect of salt stress on cucumber.